Bioresorbable Scaffolds with Biocatalytic Chemotherapy and In Situ Microenvironment Modulation for Postoperative Tissue Repair. (4th March 2021) - Xue, Chen‐Cheng; Li, Meng‐Huan; Sutrisno, Linawati; Yan, Bei‐Bei; Zhao, Yang; Hu, Yan; Cai, Kai‐Yong; Zhao, Yanli; Yu, Shu‐Hong; Luo, Zhong
Abstract: New biomaterials with antitumor and tissue repair function have become increasingly important for the postoperative care of melanoma surgery, which could prolong the tumor‐free survival of patients while simultaneously facilitating the reconstruction of the trauma tissue. For this purpose, a bioresorbable composite scaffold is designed which is fabricated by depositing therapeutic amorphous calcium carbonate (ACC)‐based nanoformulations in gelatin/polycaprolactone (GP) nanofibers via electrospinning. The ACC nanoformulations are integrated with Fe 2+ ‐preactivated bleomycin to deliver biocatalytically enhanced therapeutic effect while the hydrolysable ACC contents can act as proton scavengers to ameliorate the tumor tissue acidity in situ, leading to sustained inhibition on tumor recurrence and metastasis. The acid‐triggered ACC decomposition also releases Ca 2+ to activate the downstream Wnt/β‐catenin signaling pathways, which can cooperate with the healing effect of the GP substrate and accelerate wound regeneration. The nanoengineered scaffold can be useful as a supplementary treatment for the postoperative management of melanoma. Abstract : This study reports a bioresorbable nanocomposite scaffold as dressing materials for the treatment of surgical wounds after melanoma removal, which could inhibit the growth and metastasis of melanoma cells to prolong the tumor‐free survival of melanoma‐bearing mice while simultaneously facilitating the reconstruction of the trauma tissue, thus providing a cooperative benefit to overcome the clinical challenges associated with melanoma surgery.